Perkembangan Keagamaan Fase Usia Baligh Perspektif Ibnu Qoyyim Al-Jauziyah - Syaiful; Abas Mansur Tamam; Akhmad Alim (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The rise of books and theories of human development written by psychology experts from both western and Islamic scientists has encouraged writers to contribute to writing theories of religious development experienced by a person when they reach puberty. We still encounter children in society who have reached puberty but are not yet fully aware of their obligations in practicing religious law. This prompted the author to conduct an analysis regarding religious obligations in the puberty phase. An overview of this religious development as explained in the Al-Qur'an and Al-Hadith, with reference to the Book of Tuhfatu al-Maudud fi Ahkami al-Maulud chapter ahkamuhu 'inda Bulughihi al-'Asyirotu by Ibnu Qoyyim Al-Jauziyah. This research aims to analyze the phases of puberty based on the Al-Qur'an and Hadith which are then completed and clarified by a literature review referring to the book by the 7th century AH scholar, Ibnu Qoyyim Al-Jauziyah, and equipped with several references from books and journals relevant to the title. This research uses library research with the object of research being the Book of Tuhfatu al-Maudud fi Ahkami al-Maulud chapter ahkamuhu 'inda Bulughihi al-'Asyirotu by Ibnu Qoyyim Al-Jauziyah. The results obtained from this research are a written work that can be used as a guide for the general public in guiding the awareness of practicing their religion in children of puberty, which includes the initial steps in introducing religious cognition and daily worship practices until the end of their lives.